The structural characteristics and influential factors of psychological stress of urban residents in Jiangxi province during the COVID-19 pandemic: cross sectional study. Issue 8 (August 2021) - Huang, Zewen; Zhang, Lejun; Wang, Junyu; Xu, Lu; Li, Yin; Guo, Ming; Ma, Jingbo; Xu, Xi; Wang, Biyi; Lu, Heli
Abstract: Aims: To explore the structural characteristics and influential factors of psychological stress of urban residents in Jiangxi province during the COVID-19 pandemic through a survey of psychological stress, personality traits, family function and life satisfaction. Methods: By the convenient sampling, 1422 urban residents from Jiangxi province were assessed with Eysenck Personality Questionnaire Short Scale (EPQ-RSC), Psychological Questionnaires for Emergent Events of Public Health (PQEEPH), Family APGAR Scale (APGAR) and Satisfaction With Life Scale (SWLS). The relation among personality traits, psychological stress, family function and life satisfaction during the COVID-19 pandemic was analyzed by using the canonical correlation analysis and the serial mediation model. Results: (1) Among the estimated correlation coefficients, the first two pairs were significant ( P < 0.001 in each). (2) In the first pair of canonical variables, the loadings of neuroticism and neurasthenia were the higher (0.94, 0.70). (3) Neuroticism and life satisfaction mediated the relationship between family function and neurasthenia ( β neuroticism = -0.174; 95%CI:-0.224, -0.134; β life satisfaction = -0.034, 95%CI:-0.012, -0.062), respectively. In addition, serial mediation analyses indicated that the association of family function and neurasthenia is mediated by neuroticism and life satisfaction in a sequential manner ( β = -0.010; 95%CI:-0.020, -0.004). Conclusions: During the COVID-19 pandemic, neuroticism was closely related to psychological stress of urban residents, especially neurasthenia. In addition, the serial mediating effect of neuroticism and life satisfaction played an important role in the process of family function influencing neurasthenia. These findings contributed to a more comprehensive understanding of the influential factors for psychological stress of urban residents during the COVID-19 pandemic. Abstract : COVID-19 pandemic; Urban residents; Psychological stress; Neuroticism; Neurasthenia; Family function; Life satisfaction.